Exploring the nexus between poverty line, minimum wage, and welfare: Evidence from Indonesia's industrial labor - Syafitri, Wildan; Fitanto, Bahtiar; Setyanti, Axellina Muara (Universitas Muhammadiyah Yogyakarta, 2024)
Despite the industrial sector's critical role in Indonesia's economy, many workers remain trapped in low-welfare categories, influenced by factors such as insufficient access to digital resources, urban-rural disparities, and persistent gender and marital status inequalities. Understanding the determinants of labor welfare in this sector is essential to effectively addressing these disparities. This research examines labor welfare in Indonesia's industrial sector and identifies the key determinants by analyzing individual characteristics. The study uses generalized ordered logit, categorizing three welfare groups: those who are poor and earn below the minimum wage, those who are not poor but earn below the minimum wage, and those who are not poor and earn above the minimum wage. Data from the Survei Sosial Ekonomi Nasional (SUSENAS) provides a comprehensive foundation for the analysis. The findings reveal that internet utilization, urban residency, and age significantly increase the likelihood of being in the highest welfare category, with internet users, urban dwellers, and older workers having higher probabilities of better welfare outcomes. Gender also plays a role, as men are more likely than women to be in the higher welfare categories. Married individuals, conversely, have lower odds of being in higher welfare categories, while education shows no significant impact on welfare status. These findings suggest that enhancing internet access and digital inclusion across the workforce could significantly improve labor welfare, particularly for industrial workers. Additionally, targeted policies addressing the unique challenges of married workers and promoting regional economic equity could ensure broader and more inclusive improvements in worker well-being.